Crosstalk between glucocorticoids and IL-4 modulates Ym1 expression in alternatively activated myeloid cells - Ng Kuet Leong, Nathalie; Dalpke, Alexander; Weitnauer, Michael (Immunobiology, 2017)
Airway epithelial cells induce a tolerogenic microenvironment by modulating immune cells in the lung. We recently showed that the supernatant of airway epithelial cells induces two marker genes of alternative activation, Ym1 and Ms4a8a, in respiratory myeloid cells.